Desempenho das sementes em condição de campo, correção de stand e correlações entre algumas características das sementes de soja (Glycine mas (L) Merrill - Camargo , Ivo Marcos; Sediyama, Tuneo; Lima Thiébaut, José Tarcísio; Silva Reis , Múcio; Ferreira da Silva, Roberto (Revista Ceres, 2025)
Seeds of different quality and vigor were obtained from the harvest 4 soybean cultivars — Santa Rosa, UFV-1, UFV-2 and UFV-72-3 line — at 4 time intervals after the R8 stage was reached.